Risk Analysis of Climate Induced Disaster in Coastal Bangladesh: Study on Dashmina Upazila in Patuakhali District - Faisal, Md.; Saha, Milton Kumar; Biswas, A. K. M Abdul Ahad (TDMRC, Universitas Syiah Kuala, 2023)
The coastal region of Bangladesh is highly vulnerable to climate change and climate-induced natural disasters. Almost every year, the coastal people face different kinds of natural disasters like floods, tropical cyclones, tornadoes, tidal surges, droughts and large-scale river erosion. The main aim of this study was to identify, analyse and prioritize the existing climate-induced risks in the study area. This study was carried out in Dashmina Upazila under Patuakhali District in the southern coastal region of Bangladesh. The information has been collected through direct observations, key informant interview, focus group discussion and literature review. The study finds the ranking of various hazards based on their perceived level of impact and severity. Storm surge holds the highest ranking at number one, indicates significant devastation and danger. Following closely behind are cyclones, river bank erosion and floods, ranked at two, three, and four, respectively. Hazards such as storm winds and high tides hold moderate rankings at five and six, indicating their potential for damage but to a slightly lesser extent. Pest attacks, irregular rainfall, and hail storms fall in the mid-range of severity, ranked at seven, eight, and nine, respectively. Lastly, salinity is ranked at ten. The study suggests that the identified disaster risk should consider in time of decision making for planning any development project for disaster risk reduction and the study serves as a guide for prioritizing preparedness and mitigation strategies and allocates resources to tackle higher-ranked hazards that pose greater threats to the community or environment.